Characterization of the Hydrochlorothiazide: β-Cyclodextrin Inclusion Complex. Experimental and Theoretical Methods - Onnainty, Renée (2012)
Hydrochlorothiazide (HCT) is one of the most commonly prescribed antihypertensive drugs. In an attempt to gain an insight into the physicochemical and molecular aspects controlling the complex architecture of native β-cyclodextrin (β-CD) with HCT, we performed multiple-temperature−pH isothermal titration calorimetric measurements of the HCT: β-CD system, together with proton nuclear magnetic resonance spectroscopy (1 H NMR), phase solubility analysis, and molecular modeling methods. The AL-type diagrams, obtained at different pH values and temperatures, suggested the formation of soluble 1:1 inclusion complexes of β-CD with HCT. The corresponding stability constants (K1:1) were determined by phase solubility studies and compared with those obtained by ITC, with good agreement between these two techniques being found. The three-dimensional array of the complex was studied by 1 H NMR and molecular modeling methods. Both techniques confirmed the formation of the inclusion complex, with good agreement between the experimental and theoretical techniques regarding the HCT binding mode to β-CD. Also, the forces involved in the association process were determined, both from the thermodynamic parameters obtained by ITC (association enthalpy, binding constant, Gibbs free energy, and entropy) and from energetic decomposition analyses derived from computational methods. We concluded that the formation of the HCT:β-CD complex was enthalpy driven, with the inclusion mode of HCT being highly dependent on its ionization state. In all cases, sustained hydrogen bond interactions with hydroxyl groups of β-CD were identified, with the solvation energy limiting the affinity. Regarding the pH and temperature dependence, lower affinity constants were found at higher HCT ionization states and temperatures.